Relações biométricas de Stomolophus cf. meleagris e Lychnorhiza lucerna (Cnidaria: Discomedusae) e variação temporal de Scyphozoa em um estuário da costa paraense - BANHA, Thomás Nei Soto (2019)
The phylum Cnidaria is one of the most conspicuous of the marine environment, with more than 3,700 species from the Subphylum Medusozoa. Biometric relationships, especially those between weight and length are important parameters in population studies, in stocks estimates, ecophysiological conditions, and intra- and inter-population comparisons. The temporal variability on the occurrence of scyphozoans jellyfish in the São Caetano de Odivelas estuary, as well as the biometric relationships of Stomolophus cf. meleagris and Lychnorhiza lucerna were the scopes of this study. Samples were took in São Caetano de Odivelas, Pará, where the Mocapajuba marine protected area is located. Qualitative samples were monthly taken from April 2013 to July 2015. The specimens were obtained through manual collection on fish traps named as “curral”. Salinity was determined through a manual refractometer and rainfall data were acquired through the National Water Resources Information (SNIRH). The jellyfish volume was calculated by water displacement and biometric measurements were made using a caliper. The wet and dry weights were measured using a precision scale. The estimated curve of each biometric relationship was adjusted from non-linear regression. A total of 110 Stomolophus cf. meleagris (SM), 114 Lychnorhiza lucerna (LL), and 4 Chrysaora lactea (CL) were collected. There was a higher frequency of organisms in the dry season, due to increased penetration of marine water in the estuary and low swimming ability of the organisms. All equations showed high values of coefficient of determination (R²). Using the R² values as parameters, we observed that the Volume x Wet weight ratio was the most concise. However, using R² and R² adjusted from the residue of the equations, it can be deduced that the most suitable relationship was Volume x Dry Weight. Several factors like the sampling method may have influenced the outcome of the equations. This is the first time-series studies concerning scyphozoan jellyfish in the Amazon, although longer series and additional sampling methods must be explored to improve the knowledge on dynamics and variability of jellyfish in Amazonian estuaries.